Answer:
y - 6 = -(x + 5)
Step-by-step explanation:
Point-slope form of a linear equation is written as:
[tex]y-y_1=m(x-x_1)[/tex], where [tex](x_1,y_1)[/tex] is the point and m is the slope
Here, we're given two points: (-5, 6) and (0, 1). We need to find the slope, m. To do so, remember that slope is simply the change (or difference) in y-coordinates divided by the change (or difference) in x-coordinates. So:
m = (6 - 1) ÷ (-5 - 0) = 5 ÷ (-5) = -1
Thus, the slope is -1.
Now, let's just choose (-5, 6) as our point and plug -5 in for [tex]x_1[/tex], 6 in for [tex]y_1[/tex], and -1 in for m:
[tex]y-y_1=m(x-x_1)[/tex]
[tex]y-6=-1(x-(-5))[/tex]
y - 6 = -1(x + 5)
y - 6 = -(x + 5)
~ an aesthetics lover